(untitled) (Research, Society and Development, 2021)
The use of plant growth regulators that increase ethylene production is a common strategy to anticipate fruit ripening, increase peel color, and reduce the number of collections to complete the harvest of the fruits. Besides, this strategy may come true as a helping technique for the farmers to reduce costs with manpower, increasing overall profitability. This work aimed to evaluate the application of several concentrations of ethephon, associated with boric acid, on the anticipation of ripening of ‘Fortune’ plums, cultivated in Serra Gaúcha region, South Brazil. The study was carried out in a commercial orchard during the 2018-2019 and 2019-2020 harvests. It was used a completely randomized design with six treatments and four replicates; each replicate was composed of four plants. The following parameters were evaluated: the amount of fruits collected in each harvest, average fruit mass, diameter, length, firmness, soluble solids content, titratable acidity, SS/TA ratio, total phenolic compounds, and total anthocyanins. According to the results, the application of ethephon was capable of hastening and homogenizing partially plum ripening, but it also caused a reduction of anthocyanin and phenolic compounds contents and fruit firmness. On the other hand, the application of boric acid increased fruit firmness. From an economic standpoint, the pre-harvest application of ethephon may be interesting to reduce manpower requirements during harvest by an earlier harvest and by reducing the number of harvest cycles.